Epileptic chorea: Another window into neural networks? - Gameleira, Fernando Tenório (2018)
Paroxysmal abnormalities of motor or non-motor function are defined as epileptic when they co-occur with specific patterns of organized electrical activity as measured by scalp electroencephalography (EEG). Certain forms of abdominal pain and migraine may be therefore epileptic [1]. Stereotypical movements at night can be the result of mesial frontal epilepsy, despite a negative EEG and prolonged focal paroxysmal dystonia can result from unilateral putaminal hemorrhage [2]. Short-lasting motor activity categorized clinically as dystonia or athetosis, meeting criteria for paroxysmal non-kinesigenic dyskinesia (PNKD), may result from caudate nucleus rather than cortical discharges [3,4]. These examples suggest that epileptic activity affecting different neural networks may manifest unique motor and non-motor clinical phenotypes, beyond the classic myoclonic or tonic-clonic motor phenomena attributed to cortical epilepsy. To this end, using video-EEG, we documented ictal discharges in the left temporal lobe of a patient with episodic chorea, initially suspected to be within the PNKD spectrum, suggesting that paroxysmal chorea can also be of epileptic origin in a subtype of patients.